Unleashing the Potential: Exploring the Application and Mechanism of Mesenchymal Stem Cells in Autoimmune Diseases - Xinqi Li; Rongli Li; Jialing Huang; Yuelin Hu; Chenxi Fan; Xin Wang; Hongsong Yu (Stem Cells International)
Autoimmune diseases (AIDs) occur when the immune system mistakenly attacks the body’s own antigens. Traditionally, these conditions are treated with nonspecific immunosuppressive therapies, including corticosteroids, immunosuppressants, biological agents, and human immunoglobulins. However, these treatments often fail to achieve optimal outcomes, especially for patients with severe cases. Mesenchymal stem cells (MSCs) present a promising alternative due to their robust self-renewal capabilities and multidirectional differentiation potential. MSCs are easily accessible, exhibit low immunogenicity, and can help reduce graft rejection. MSCs can inhibit T cell proliferation, reduce proinflammatory T cells, inhibit B cell differentiation, induce macrophage polarization towards the anti-inflammatory M2 phenotype, and suppress activity of natural killer (NK) cells and dendritic cells (DCs). Additionally, MSCs can regulate T cells, macrophages, and fibroblast-like synoviocytes (FLS) by releasing microRNA (miRNA) through exosomes or extracellular vesicles (EVs), thus providing therapeutic benefits for various diseases. Numerous clinical trials have highlighted the therapeutic benefits of MSCs in treating various AIDs, leading to increased interest in MSC transplantation. This review summarizes the current applications and mechanisms of action of MSCs in the treatment of AIDs.